Causal associations between the insulin-like growth factor family and sarcopenia: a bidirectional Mendelian randomization study - Liu, Jili; Chen, Meng; Xia, Xin; Wang, Zhaolin; Wang, Yanqin; Xi, Ling (Frontiers in Endocrinology, 2024)
Objective Insulin-like growth factor (IGF) is closely associated with sarcopenia, yet the causal relationship of this association remains unclear. This study aims to explore the potential causal relationship between members of the IGF family and sarcopenia from a genetic perspective through bidirectional Mendelian randomization (MR) analysis using two-sample datasets. Methods Five genetically predicted factors of the IGF family (IGF-1, IGF-1R, IGF-2R, IGFBP-3, IGFBP-7) as one sample, while four relevant features of sarcopenia (low hand grip strength, appendicular lean mass, whole body fat-free mass, and walking pace) as another sample, in conducting a two-sample MR analysis. Results The forward MR results of the relationship between IGF and sarcopenia showed that elevated levels of IGF-1 reduced the risk of low hand grip strength (OR = 0.936, 95% CI=0.892-0.983, P = 0.008) and increased appendicular lean mass of the extremities and whole body fat-free mass (OR = 1.125, 95% CI=1.070-1.182,P = 0.000; OR =1.076, 95% CI=1.047-1.106, P=0.000), reduced the risk of sarcopenia. Elevated IGF-1R also favored an increase in whole body fat-free mass (OR=1.023, 95% CI=1.008-1.038, P =0.002), and the appendicular lean mass trait was more pronounced with elevated IGFBP-3 and IGFBP-7 (OR=1.034, 95% CI=1.024-1.044, P =0.000; OR=1.020, 95% CI=1.010-1.030, P=0.000). Inverse MR results of the effect of sarcopenia on IGF showed that decreased hand grip strength may elevate IGF-1 levels (OR=1.243, 95% CI=1.026-1.505,P =0.027), whereas improvements in appendicular lean mass, whole body fat-free mass traits, and increased walking pace decreased IGF-1 levels (OR=0.902, 95% CI: 0.877-0.927, P = 0.000; OR=0.903, 95% CI=0.859-0.949,P = 0.000; OR=0.209, 95% CI=0.051-0.862,P = 0.045). Also decreased hand grip strength may elevate IGF-1R levels (OR=1.454, 95% CI=1.108-1.909, P =0.007), and appendicular lean mass stimulated high expression of IGFBP-1 (OR=1.314, 95% CI=1.003-1.722, P =0.047). Heterogeneity and pleiotropy were not detected in all results, and the results were stable and reliable. Conclusion There is a bi-directional causal association between IGF family members and the risk of sarcopenia, which provides a more adequate basis for early biological monitoring of sarcopenia and may provide new targets for early intervention and treatment of sarcopenia.